Association of Drug Burden Index with Grip Strength, Timed Up and Go and Barthel Index Activities of Daily Living in Older Adults with Intellectual Disabilities: An Observational Cross-sectional Study - Burke, Eilish; O'Dwyer, Maire; Henman, Martin (My University, 2019)
Background: Drug Burden Index (DBI), a measure of exposure to medications with anticholinergic and sedative activity, has been associated with poorer physical function in older adults in the general population. While extensive study has been conducted on associations between DBI and physical function in older adults in the general population, little is known about associations in older adults with intellectual disabilities (ID). This is the first study which aims to examine the association between DBI score and its two sub-scores, anticholinergic and sedative burden, with two objective measures of physical performance, grip strength and timed up and go, and a measure of dependency, Barthel Index activities of daily living, in older adults with ID. Methods: Data from Wave 2 (2013/2014) of the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing (IDS-TILDA) was analysed. Analysis of Covariance (ANCOVA) was used to detect associations and produce adjusted means for the physical function and dependency measures with respect to categorical DBI scores and the anticholinergic and sedative sub-scores (DBA and DBS). Results: After adjusting for confounders (age, level of ID, history of falls, comorbidities and number of non-DBI medications, Down syndrome (grip strength only) and gender (timed up and go and Barthel Index)), neither grip strength nor timed up and go were significantly associated with DBI, DBA or DBS score > 0 (p > 0.05). Higher dependency in Barthel Index was associated with DBS exposure (p < 0.001). Conclusions: DBI, DBA or DBS scores were not significantly associated with grip strength or timed up and go. This could be as a result of established limitations in physical function in this cohort, long-term exposure to these types of medications or lifelong sedentary lifestyles. Higher dependency in Barthel Index activities of daily living was associated with sedative drug burden, which is an area which can be examined further for review.
PUBLISHED
Keywords: Drug Burden Index (DBI); anticholinergic and sedative activity; older adults with intellectual disabilities (ID); Ageing; Anticholinergic; Barthel index; Grip strength; Intellectual disability; Medication; Physical function; Sedative; Timed up and go; Ageing; Ageing, Health and Intellectual Disability; Age-related disability; Intellectual Disability; Health